A quantized mechanism for activation of pannexin channels - Yu-Hsin Chiu (Nature Portfolio, 2017)
Pannexins are oligomeric plasma membrane channels that allow permeation of ions and large molecules. Here the authors show that human Pannexin 1 activation is a multistep event, where modification of each monomer opens the channel to a unique conductance state and fine tunes its activity.